Sense of place: trends from the literature. Issue Volume 13:Issues 2(2020) (2nd April 2020) - Nelson, Jake; Ahn, Jeong Joo; Corley, Elizabeth A.
ABSTRACT: Scholars studying sense of place have introduced several separate yet related terms which are often used interchangeably including phrases like place attachment, place meaning, place identity, and place dependence. Given the lack of a coherent understanding for sense of place in the literature, it is challenging to study and operationalize the concept in a consistent way. In this study, we use publication data and citation data to clarify how sense of place has been defined and applied. Our findings show that sense of place has evolved over time, although it is in the last decade that scholarship has grown considerably. We also find that the dimensions used to define and measure the concept have changed with time and discipline. These results imply that scholars need to study sense of place in careful consideration of the dimensions that they want to investigate and the disciplinary context each study is embedded in.